2018
DOI: 10.3389/fphys.2017.01117
|View full text |Cite
|
Sign up to set email alerts
|

Obesity or Overweight, a Chronic Inflammatory Status in Male Reproductive System, Leads to Mice and Human Subfertility

Abstract: Obesity is frequently accompanied with chronic inflammation over the whole body and is always associated with symptoms that include those arising from metabolic and vascular alterations. On the other hand, the chronic inflammatory status in the male genital tract may directly impair spermatogenesis and is even associated with male subfertility. However, it is still unclear if the chronic inflammation induced by obesity damages spermatogenesis in the male genital tract. To address this question, we used a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 51 publications
3
68
1
2
Order By: Relevance
“…21 The present histopathological result of HFD feeding is comparable to earlier studies of HFD-induced testicular injury; the HFD fed rats' revealed degeneration in testicular morphology, characterized as atrophied seminiferous tubules, disruption in spermatogenesis and vacuolation of germinal epithelium, this is contestant with previous studies who demonstrated atrophied seminiferous epithelia, coalescence between spermatogenic cells and impaired and loosely organized Sertoli cells in mice fed HFD. 22 Atrophied seminiferous tubuli were also observed in HFD treated rats associated disconnection of the degenerated STs from the interstitial wall with increased area of the connective tissue and remarkable apoptotic activity in Leydig and Sertoli cells. 9 Vacuolar alterations in seminiferous tubules, spermatogenic cell dysfunction, and increased apoptosis of spermatogenic cells in testicular tissue was also observed in HFD treated rats.…”
Section: Discussionmentioning
confidence: 97%
“…21 The present histopathological result of HFD feeding is comparable to earlier studies of HFD-induced testicular injury; the HFD fed rats' revealed degeneration in testicular morphology, characterized as atrophied seminiferous tubules, disruption in spermatogenesis and vacuolation of germinal epithelium, this is contestant with previous studies who demonstrated atrophied seminiferous epithelia, coalescence between spermatogenic cells and impaired and loosely organized Sertoli cells in mice fed HFD. 22 Atrophied seminiferous tubuli were also observed in HFD treated rats associated disconnection of the degenerated STs from the interstitial wall with increased area of the connective tissue and remarkable apoptotic activity in Leydig and Sertoli cells. 9 Vacuolar alterations in seminiferous tubules, spermatogenic cell dysfunction, and increased apoptosis of spermatogenic cells in testicular tissue was also observed in HFD treated rats.…”
Section: Discussionmentioning
confidence: 97%
“…The past decade has witnessed many studies, which suggested that the malfunction of NLRP3 inflammasome is a potent trigger of a series of autoinflammatory and autoimmune diseases, including gout, rheumatoid arthritis, and lupus . Moreover, NLRP3 inflammasome has been reported to participate in the chronic inflammation status in the prostate …”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, NLRP3 inflammasome has been reported to participate in the chronic inflammation status in the prostate. [13][14][15] Alcohol consumption is widespread all over the world. Alcohol use disorders extensively exist globally.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the testis, TNF-α, IL-1β, and IL-6 were associated with a dose-dependent decline in steroidogenesis in TM3 Leydig cells [64]. Furthermore, in rat models of diet-induced obesity, high levels of TNF-α, IL-1β, and IL-6 were associated with the disruption of testicular morphology, with a reduction in seminiferous tubule diameter, epithelial and germ cell atrophy and apoptosis, abnormal adhesions between Sertoli and spermatogenic cells and the blood-testis barrier disassembly [65]. On the other hand, even if IL-8 exerts a stimulating effect on TM3 Leydig cell growth, it appears to minimally affect T production and blood concentrations [64].…”
Section: Other Pro-inflammatory Cytokinesmentioning
confidence: 96%